Histórias de uma aluna surda, um professor-intérprete de Libras e o currículo vivido na escola. - Oliveira, Thiago Lemes de (2025)
In this dissertation, I narratively analyze the experience of living and constructing the curriculum with a deaf student in the early grades of Elementary School. Narrative Inquiry, in the perspective of Clandinin and Connelly (2000; 2011), with an ontological basis in experience according to the studies of John Dewey (1979; 2011), guides the theoretical-methodological path of this research, enabling the meaning making process and discussion about experiences and the stories lived by, more specifically my stories as a teacher-interpreter of LIBRAS and narrative inquirer, and Nina's, the deaf student whom I accompanied as a participant in the research. I remember one day in the first week of school when I arrived 5 minutes late due to traffic. Nina was already in the classroom; the lead teacher was sitting at her desk organizing some activities, while the other students were talking, playing, and running between the rows of desks. Nina was standing, observing all the activity in the room, with a calm expression. I asked if everything was okay, and she said yes. I then asked if she was worried that I hadn’t arrived, and she looked at me with an expression as if she didn’t understand. I repeated the question, and she placed her hand on her head, moving it to indicate that she didn’t understand what I was asking. I used mime and body-facial expressions to make myself understood. When she finally understood what I was trying to ask her, she calmly replied that she had been waiting for me. I became anxious, questioning whether she didn’t know the signs I had made or if she didn’t know LIBRAS. A few minutes later, the teacher told the class that there was a new student in the room and asked her to introduce herself. I interpreted for Nina and waited for her to say her name. To my surprise, she again shook her head, indicating she had not understood. Then, I pointed to myself and spelled my name in LIBRAS: T-H-I-A-G-O. I pointed to the teacher, who was observing the whole situation, and spelled her name. Then, I pointed to Nina and made an interrogative expression, raising my eyebrows, shrugging my shoulders, and opening my hands with palms up. Nina then pointed to herself and spelled: N-N-A. I translated her name for the teacher and the classmates. But that missing letter ruined my day. That missing letter meant much more than just a language conflict. Nina was not literate in LIBRAS nor in Portuguese. How had a 10-year-old girl reached the third grade of elementary school without being able to read or write in Portuguese, and, more importantly, without knowing how to communicate with those around her? How could I communicate with her? How could I do my job of helping her learn when she didn’t understand what I was translating or teaching? What was her understanding of the world? What were her knowledges, and how could I access them? How would my relationship with Nina influence her development and learning? What meanings would we construct from our experiences and lives? Thus, as a narrative inquirer and participant in this research, in an attempt to answer these questions, I address in this thesis issues such as inclusion and exclusion, curriculum as a flow of events, the familial curriculum making, ethics of care and relational ethics, teaching and didactic adaptation, translation and interpretation during the teaching and learning process in the classroom in a public school.